2017
DOI: 10.12659/msm.901876
|View full text |Cite
|
Sign up to set email alerts
|

Position of Immobilization After First-Time Traumatic Anterior Glenohumeral Dislocation: A Literature Review

Abstract: Anterior glenohumeral dislocation affects about 2% of the general population during the lifetime. The incidence of traumatic glenohumeral dislocation ranges from 8.2 to 26.69 per 100 000 population per year. The most common complication is recurrent dislocation occurring in 17–96% of the patients. The majority of patients are treated conservatively by closed reduction and immobilization in internal rotation for 2–3 weeks. However, no clear conservative treatment protocol exists. Immobilization in external rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
0
8
0
3
Order By: Relevance
“…Reports of external rotation are not unanimously favorable. A recent literature review of the position of immobilization after first-time traumatic anterior shoulder dislocations found that external rotation posed no superiority to internal rotation [42]. Although external rotation did result in better coaptation of the labrum and glenoid fossa, there were no significant differences in dislocation recurrence rates or patient quality of life.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports of external rotation are not unanimously favorable. A recent literature review of the position of immobilization after first-time traumatic anterior shoulder dislocations found that external rotation posed no superiority to internal rotation [42]. Although external rotation did result in better coaptation of the labrum and glenoid fossa, there were no significant differences in dislocation recurrence rates or patient quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…Although external rotation did result in better coaptation of the labrum and glenoid fossa, there were no significant differences in dislocation recurrence rates or patient quality of life. It is speculated that external rotation immobilization may be the method of choice for patients with a specific labroligamentous injury with anterior shoulder dislocation, but research-supported conclusions are yet to be determined [42]. It has been suggested external rotation immobilization should only be considered in highly motivated, compliant patients who are informed of the discomfort and possible difficulties with everyday tasks while the brace is being used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No entanto, estudos mais recentes têm falhado em demonstrar a superioridade de um tipo de imobilização sobre a outra em relação à diminuição da taxa de recorrência e melhoria da qualidade de vida dos pacientes. 13 Em relação à duração, a imobilização por um período superior a uma semana não demonstrou superioridade na taxa de recorrência em relação à imobilização por períodos mais curtos. Neste contexto a individualização do tratamento tendo em conta o controlo álgico parece ser a melhor estratégia.…”
Section: Palavras-chave / Abstractunclassified
“…2 Por outro lado, a intervenção cirúrgica, nomeadamente artroscópica está recomendada nos doentes com menos de 30 anos de idade, nos atletas de elevado nível 19 e na presença de lesão de Hill-Sachs. 13 A instabilidade recorrente, a perda de massa óssea e o final da época têm sido critérios para a realização da cirurgia. 18 A intervenção cirúrgica proporciona menores taxas de recorrência 20 , mas obriga a maior tempo de paragem até ao Return to play (RTP), cerca de 4 a 6 meses 4 , durante os quais existem várias fases: 1 -imobilização durante quatro semanas com contrações isométricas; 2 -mobilização ativa do ombro até 45 graus de rotação externa durante mais 4 semanas; 3 -mobilização ativa do ombro em toda a amplitude articular, com treino de resistência e de pliometria, e também da propriocetividade.…”
Section: Introductionunclassified